TRILOGI DALAM MEMBANGUN SEKOLAH UNGGUL: Kepemimpinan, Budaya Mutu, Benchmarking - Mustajab Mustajab (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2015)
Improved quality is becoming increasingly important for an educational institution in order to obtain better control through their own efforts. Moreover, today, the demand for educational institutions to be able to provide quality education services for students. The process that was first in establishing a school culture based on the quality of the school. Elements that must be built into the school culture as work culture, performance and discipline of implementing school (teachers, staff and principals). Executing school always eager to go forward, eager continues to add capabilities and skills which will ultimately improve their performance. Quality of institutions is influenced by the extent to which leadership can direct the organization's activities, both visible (tangable) or invisible (intangable) to build a strong quality. Here the leader is required to manage the elements of the quality of the institution as a manifestation in the form of beliefs, values and behaviors of all members. In building quality in primary schools to internalize things in a work culture that values quality foundation that is ethics, integrity, trust, communication, and recognition. Then the principal's role in building a quality school requires a strong commitment by involving members or individuals in the school environment. The next process in the development of quality culture which is the principal along with school staff andstakeholders do the reviews carefully and objectively. Starting from school review then the school should establish benchmarking and followed up with a quality control (quality control). In a sense, -after set ideal performance, - the principal along with the staff should try to do quality control by comparing the actual performance with the ideal performance (benchmarking). Conversely, if the actual performance has reached the ideal performance, it must be done to improve the quality (benchmarking) higher in a sustainable manner. If this is done constantly, the head of the school will be ready and able to assure the quality of schools (quality assurance).